Localized congenital erosive vesicular dermatosis healing with elastic reticulated scars. - Hunashikatti, V.B.; Srinivas, S.M. (European Journal of Pediatric Dermatology, 2025)
Congenital erosive vesicular dermatosis (CEVD) healing with elastic reticulated scars is a rare condition that predominantly affects premature infants and presents at birth with vesicles and erosions. The lesions usually heal within a few months, leaving a characteristic supple and reticulated scar. It affects 75% of the body surface, sparing the palms and soles. In the current work, we present a case in a full-term child with a localized form of CEVD of the scalp associated with posterior fossa cysts and an atrial septal defect.